Water, Food and Welfare Water Footprint as a Complementary Approach to Water Management in Mexico - Perez-Espejo, Rosario H.; Constantino-Toto, Roberto M.; Davila-Ibanez, Hilda R. (SpringerBriefs in Environment, Security, Development and Peace, 2016)
This book addresses the following topics: the contemporary model for water management and alternative approaches; the socioeconomic framework, water policy and institutions; water use for food purposes, water-resources inventory and irrigation; manifestations of welfare loss and water prices; change in dietary patterns and water security; hydrological stress and pressures on water availability; groundwater management problems; vulnerability and climate change; water demand of major crops; gray water footprint and water pollution; gray water footprint and mining; virtual water and food trade; estimates of the water footprint of four key cereals, forage, livestock and bottled drinks. It is the result of a cooperation between 16 researchers from eleven Mexican academic institutions.